A systematic review on the impact of green management on construction firms' financial performance - Mingyi, Ying; Sai Hong, Tang; Elianddy B. Supeni, Eris; Yingqiao, Xia; Yujia, Ying (Human Resources Management Academic Research Society (HRMARS), 2024)
This paper systematically examines the significant impact of green management on the financial performance of construction firms. By conducting a thorough literature review and detailed qualitative analysis, the study aims to offer valuable insights for the construction industry, helping it to pursue sustainable development while maintaining economic viability. The research explores how different green management practices—such as using sustainable materials, implementing energy-efficient construction methods, and obtaining environmental certifications—affect financial performance. The findings indicate that although initial investments in green technologies can be financially challenging, the longterm benefits, including operational cost savings, improved reputation, and greater market competitiveness, far outweigh these initial expenses. The study encourages the integration of green management into the strategic planning of construction firms to achieve both environmental and financial success.